The Effect of Reproductive Factors on Coronary Artery Disease in Women - Darvish, Soodabeh; Sadeghian, Saeed; Ghaseminejad, Azizeh; Mohebi, Reza (Advances in Nursing & Midwifery, 2019)
Abstract Introduction: There is a sex discrepancy in cardiovascular physiology. In this study, we aimed to investigate the effect of female reproductive factors on coronary artery disease (CAD) beyond the known CAD risk factors. Methods: In a case-control study, women referred to Tehran Heart Center for coronary artery angiography from 2012 to 2014 were enrolled. Of these, 80 premenopausal and 100 postmenopausal females with CAD in angiography were randomly selected as cases and 80 premenopausal and 100 postmenopausal females without CAD in angiography were selected as controls. A questionnaire including reproductive history and known CAD risk factors was filled for every subject. Analysis was performed separately for pre and postmenopausal women and a final adjustment for coronary artery disease risk factors was done. Results: Among reproductive factors, oligomenorrhea (OR= 6.72) was a significant risk factor for CAD in premenopausal women and history of oral contraceptive (OCP) use had a protective effect on CAD in pre and postmenopausal woman (OR= 0.24 and 0.20, respectively). Conclusions: Since oligomenorrhea has a strong association with insulin resistance and diabetes, a conventional risk factor of CAD, women with oligomenorrhea should be treated not only for cyclic irregularity but also for prevention of CAD.